9514 1404 393
Answer:
m = 3
Explanation:
Notice what has been done to the variable. It has been multiplied by 3, then 1 is added to the product.
We solve an equation like this by undoing those operations, in the reverse order. First, we undo the addition of +1 by adding -1 (the opposite of +1) to both sides of the equation.
3m + 1 - 1 = 10 - 1
3m = 9 . . . . . . . . . simplify
__
Now, we undo the multiplication by 3 by multiplying by the "multiplicative inverse" or reciprocal, 1/3. This is the same as dividing by 3.
(1/3)(3m) = (1/3)(9)
As before, we do this to both sides of the equation.
m = 3 . . . . . . . . . simplify
The solution is m = 3.
_____
The rule for equations is that you must do the same operation to both sides of the equation in order for it to remain valid. (The same is true for inequalities, with a special rule for multiplication or division by a negative number. Doing that reverses the comparison symbol: < ⇔ > or ≤ ⇔ ≥.)